Loyalty the Customer: Profile of Customer Relationship Management (Hotel Case Study In West Bandung, Indonesia) - Ananta Budhi Danurdara; Rudy Parlindungan Siahaan; Ammarn Sodawan (Pusaka : Journal of Tourism, Hospitality, Travel and Business Event, 2024)
There have been many studies on customer relationship management, but those focusing on the history behind success are still minimal. This research aims to uncover customer relationship management in fostering the loyalty of Hotel X, West Bandung, West Java, Indonesia. The Bandung area, which includes Subang, has recently become a more popular tourist destination due to the construction of numerous nearby hotels. However, the rivalry is now more fierce than it was previously. In order to compare the topic under investigation with the actual conditions at Hotel X at West Bandung Regency, the researcher conducted a literature analysis on Customer Relationship Management and spoke with five managers about it. The three programs the researcher determined impacted CRM were the Partnering Program, Continuity Marketing, and One-to-One Marketing. The researcher has examined the program and connected it to theory through primary research employing qualitative approaches. While nearly every program has been implemented, Hotel X at the West Bandung Regency did not adopt a branding program, according to the results of the interview session. It is recommended that hotels conduct shortterm market and competitor research. As technology advances, so does the environment.